(untitled) (Asian Journal of Agriculture, 2023)
Abstract. Prellia A, Solichatun, Pitoyo A. 2023. Induction of drought resistance in bell pepper (Capsicum annuum var. grossum) with osmopriming Polyethylene Glycol (PEG) 4000. Asian J Agric 7: 34-46. The bell pepper (C. annuum var. grossum) is an economically valuable chili cultivar. However, in Indonesia, the cultivation of bell peppers is hampered by drought stress. Osmopriming is an alternative method to improve seed quality. That method was used by soaking the seeds in osmoticum solutions, with Polyethylene Glycol (PEG) as the solution. This research examines the effect of osmopriming with PEG 4000 on the germination and growth of bell pepper seedlings under various drought stressors. In 2020, seeds were collected from ripe bell peppers grown by farmers in Surjo Hamlet, Sukabumi Village, Cepogo Sub-district, Boyolali District, Central Java, Indonesia. This study employed a Completely Randomized Design (CRD) with two parameters: PEG concentration and water capacity variations. The concentrations of PEG 4000 utilized were 0, 50, 100, and 150 g/L. The drought stress test is conducted by cultivating primed bell pepper seedlings in planting media with varying water capacities of 100%, 75%, and 50% Space Capacity (SC). Included in the drought group with a moderate stress level is a water capacity of 50% SC. Each treatment was replicated three times. Under drought stress, osmopriming with PEG 4000 accelerated the germination rate and affected seedling growth regarding height, number of leaves, leaf area, wet seedling weight, and shoot-root ratio. However, under drought stress, osmopriming PEG 4000 had no significant effect on the rise in proline and chlorophyll content nor on the decrease in carotenoids and nitrate reductase activity. PEG 150 g/L with 50% SC was ideal for seedling height, leaf number, leaf area, and wet weight, while PEG 100 g/L with 100% SC was optimal for the shoot-root ratio.